Saphenous Vein Graft Aneurysm after Drug-Eluting Stent Implantation: Treatment by Covered Stent - Kyriacos Papadopoulos; Panayiotis Avraamides (Case Reports in Cardiology)
Saphenous vein graft aneurysms (SVGAs) occur as a rare complication of coronary artery bypass graft but increases the risk of morbidity and mortality. Atherosclerosis is considered to be the most common cause of saphenous vein graft aneurysms. Other etiologies include infections, varicosities of vein grafts, and surgical technical issues. These aneurysms usually present as an incidental finding of a mediastinal or cardiac mass on chest radiograph. Symptomatic aneurysms may present with a wide variety of clinical manifestations such as chest pain/angina, shortness of breath, and myocardial infarction. Treatment options of SVG aneurysms include surgery, percutaneous intervention (including vascular plugs, covered stents, and embolization coils), and conservative management. Herein, we describe a case of a saphenous vein graft aneurysm that developed after percutaneous intervention, which has never been described, to our knowledge, in the previous literature. The aneurysm was treated with polytetrafluoroethylene covered stent implantation.